2021
DOI: 10.3390/bios11080280
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Colorimetric Detection of Nitrite Realized by Stringing Nanozyme Catalysis and Diazotization Together

Abstract: Due to the great threat posed by excessive nitrite in food and drinking water to human health, it calls for developing reliable, convenient, and low-cost methods for nitrite detection. Herein, we string nanozyme catalysis and diazotization together and develop a ratiometric colorimetric approach for sensing nitrite in food. First, hollow MnFeO (a mixture of Mn and Fe oxides with different oxidation states) derived from a Mn-Fe Prussian blue analogue is explored as an oxidase mimic with high efficiency in catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…It is reported that TMB and oxidized TMB (TMBox) may react with nitrite through two different reaction paths and mechanisms: diazotization interaction , and redox interaction. To confirm these, a series of experiments were performed.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that TMB and oxidized TMB (TMBox) may react with nitrite through two different reaction paths and mechanisms: diazotization interaction , and redox interaction. To confirm these, a series of experiments were performed.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Besides, in some cases, logical operation on these signal outputs can be made to further boost the analytical sensitivity. 19 Consequently, multimodal methods are able to benefit the measurement of targets via expanded usage scenario and enhanced reliability as well as improved sensitivity, yet how to rationally design strategies to achieve the multimode perception of analytes is a great challenge. Nanomaterials with bioenzyme-like catalytic activities (nanozymes) have been proposed as a new generation of artificial enzymes in recent years, 20−23 exhibiting the superiorities of good stability, low cost, and easy-to-regulate activity compared to bioenzymes.…”
Section: Nitrite (Nomentioning
confidence: 99%
“…One can select an appropriate mode from multimodal methods to achieve the monitoring of targets according to matrix characteristics and testing environments, where traditional single-mode sensors may fail. On the other hand, the results obtained from different modes can be verified against each other, effectively improving the accuracy and reliability and avoiding false results. , Besides, in some cases, logical operation on these signal outputs can be made to further boost the analytical sensitivity . Consequently, multimodal methods are able to benefit the measurement of targets via expanded usage scenario and enhanced reliability as well as improved sensitivity, yet how to rationally design strategies to achieve the multimode perception of analytes is a great challenge.…”
Section: Introductionmentioning
confidence: 99%